The effect of brexpiprazole in adult outpatients with early-episode schizophrenia: an exploratory study. (November 2016) - Malla, Ashok; Ota, Ai; Nagamizu, Kazuhiro; Perry, Pamela; Weiller, Emmanuelle; Baker, Ross A.
Abstract : The aim of this study was to evaluate flexibly dosed brexpiprazole for early-episode schizophrenia through the assessment of efficacy, social functioning, and tolerability. This was an exploratory, 16-week, open-label, flexible-dose (1, 2, 3, or 4 mg/day; target dose 3 mg/day) study in outpatients with early-episode schizophrenia (18–35 years old, ⩽5 years' duration of illness). Efficacy was assessed by the Positive and Negative Syndrome Scale score (PANSS) and social functioning was assessed by changes from baseline in PANSS modified prosocial subscale, personal and social performance (PSP), and specific levels of functioning (SLOF) scales. Safety and tolerability were also evaluated. Overall, 25/49 patients completed the study. Symptoms of schizophrenia improved over the entire treatment period, as evidenced by reductions in PANSS total score from baseline (least squares mean change at week 16: −10.2). Improvements in social functioning were shown by least squares mean changes from baseline at week 16 in the PANSS prosocial subscale (−2.0), PSP (6.6), and SLOF (13.1). Brexpiprazole was generally well tolerated; the most common adverse events were insomnia (7/49 patients), somnolence (4/49), sedation, weight increase, and nausea (each 3/49). Brexpiprazole may represent a novel and effective treatment strategy for patients with early-episode schizophrenia and may be effective for improving social function.